- PEMANFAATAN LIMBAH MINYAK JELANTAH SEBAGAI SUMBER BAHAN BAKAR ALTERNATIF DALAM PRODUKSI BIODIESEL MENGGUNAKAN KATALIS CaO/rGO: - - Rohani, Siti; Mulyadi, Dikdik; Mukmilah Yuningsih, Lela (Jurnal Teknologi dan Inovasi Industri (JTII), 2025)
Heterogeneous CaO catalyst composited with rGO has been developed to improve catalytic efficiency and biodiesel yield. Used cooking oil was chosen as the feedstock because it is underutilized, while rGO was used to overcome the weaknesses of CaO, which has a small surface area, as well as to enhance catalyst activity through an increased number of active sites and catalytic stability. The purpose of this study is to increase the yield and characterize biodiesel according to SNI 04-7182-2015. Biodiesel production was carried out through the transesterification reaction of triglycerides with metanol using CaO/rGO catalyst. Variations in the molar ratio of oil to metanol (1:6, 1:9, and 1:12) and catalyst concentration (0.5% and 1%) at 55–60°C were applied to optimize the yield. The resulting biodiesel was characterized based on physical parameters, including density, viscosity, flash point, water content, and acid number according to SNI standards. The best result was obtained at a metanol to oil molar ratio of 1:12 with the addition of 1% catalyst, yielding a biodiesel yield of 89.5%, all of which met the SNI standards except for viscosity, which was lower than the SNI specification. Without catalyst at a 1:9 ratio, biodiesel yield reached only 65%. The CaO/rGO catalyst can increase biodiesel yield at a 1:12 ratio and meets SNI standards for flash point, acid number, water content, and density but does not meet the SNI standard for viscosity.